2019
DOI: 10.1021/acs.est.9b04674
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to PM2.5 Affects Fetal Lung Development at Sensitive Windows

Abstract: Lung development continues from the embryonic period to adulthood. Previous epidemiological studies have noted that maternal exposure of atmospheric pollutants during the sensitive windows disturbed the lung development and increased the risk of lung diseases after birth, but the experimental evidence was insufficient. In the present study, we exposed plug-positive mice to PM2.5 (3 mg/kg b.w.) by oropharyngeal aspiration every other day, and intended to test whether maternal PM2.5 exposure affected prenatal lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…So far, numerous studies have indisputably demonstrated that maternal exposure to nanomaterials during gestation result in fetotoxicity, including adverse prenatal effects on the fetus [10][11][12][13][14][15][16][17], neurotoxicity [18][19][20][21][22][23], reproductive toxicity [24][25][26][27][28], immunotoxicity [29][30][31][32] and respiratory toxicity [29,[33][34][35] in offspring or even in adulthood [16][17][18]36]. The direct translocation of NPs or indirect interference from maternal damage-induced maternal mediators and placental mediators contributes to the fetotoxicity induced by prenatal exposure to NPs [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…So far, numerous studies have indisputably demonstrated that maternal exposure to nanomaterials during gestation result in fetotoxicity, including adverse prenatal effects on the fetus [10][11][12][13][14][15][16][17], neurotoxicity [18][19][20][21][22][23], reproductive toxicity [24][25][26][27][28], immunotoxicity [29][30][31][32] and respiratory toxicity [29,[33][34][35] in offspring or even in adulthood [16][17][18]36]. The direct translocation of NPs or indirect interference from maternal damage-induced maternal mediators and placental mediators contributes to the fetotoxicity induced by prenatal exposure to NPs [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneity of variance (HV) among groups was analyzed with Levene’s test. A two-tailed Student’s t test was used to compare the results between two groups as we described previously . Differences in all tests were considered significant when p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution exposure during pregnancy has been linked to placental inflammation and impairment of placental function [ 67 ]. PM 2.5 exposure may cause inflammatory responses in the placenta, which may be transmitted from the mother to the fetus and contribute to the development of abnormalities [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%